2011
DOI: 10.1002/nau.21190
|View full text |Cite
|
Sign up to set email alerts
|

Overactive bladder in Taiwanese women: Re‐analysis of epidemiological database of community from 1999 to 2001

Abstract: The prevalence of OAB using the current definition is slightly higher than the result found in our previous published data using a defective classification system of OAB symptoms. The effects of mixed symptoms and probable misclassification cannot be overlooked because many women with OAB (with or without urgency incontinence) might also have SUI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 19 publications
2
23
0
Order By: Relevance
“…One Taiwanese study reported adult OAB prevalence to be 16.9%, similar to the rate of 15.8% in Taiwanese men and women in the present study. However, another study conducted in Taiwan (in women only) reported higher OAB prevalence, ranging between 21.0% and 34.8% depending on the OAB definition used . OAB prevalence rates above the levels reported herein have also been observed in 2 international Asian studies.…”
Section: Discussionsupporting
confidence: 43%
See 2 more Smart Citations
“…One Taiwanese study reported adult OAB prevalence to be 16.9%, similar to the rate of 15.8% in Taiwanese men and women in the present study. However, another study conducted in Taiwan (in women only) reported higher OAB prevalence, ranging between 21.0% and 34.8% depending on the OAB definition used . OAB prevalence rates above the levels reported herein have also been observed in 2 international Asian studies.…”
Section: Discussionsupporting
confidence: 43%
“…However, an OAB prevalence of 26.3% based on IPSS was reported in a Chinese study of men aged >50 years,17 which is comparable with the prevalence of 21.4% among Chinese men aged ≥40 years in the present study.A previous Korean study reported OAB prevalence to be 12.2%,11 below the rate of 19.7% reported herein, but this difference could be attributable to the population in the other study being aged ≥18 years.One Taiwanese study reported adult OAB prevalence to be 16.9%,16 similar to the rate of 15.8% in Taiwanese men and women in the present study. However, another study conducted in Taiwan (in women only) reported higher OAB prevalence, ranging between 21.0% and 34.8% depending on the OAB definition used 8. OAB prevalence rates above the levels reported herein have also been observed in 2 international Asian studies.…”
supporting
confidence: 44%
See 1 more Smart Citation
“…In China, however, even though Wang et al [39] adopted the ICS definition in a CS study with 14,844 persons, the overall prevalence of OAB was relatively lower (6.0%) than in other countries and nocturia was the most prevalent symptom besides urgency. Chen et al [40] reanalyzed the data from their previous CS study with 1,247 Taiwanese women in 2012 by using the ICS definition. After excluding individuals who had a single symptom such as nocturia or frequency only, the prevalence of OAB decreased from 34.8% to 20.9%.…”
Section: Epidemiology Of Oabmentioning
confidence: 99%
“…It has further been proven that autonomic system disorders are connected with OAB pathogenesis and may increase cardiovascular risk. The results of the Women's Health Initiative Observation Study revealed that hypertension was diagnosed in 42.4% of women aged 50–79, and the highest percentage of female patients suffering from OAB belongs to this age group …”
Section: Introductionmentioning
confidence: 99%